Is a Finite Life Such a Bad Idea? Transhumanism and Theological Anthropology - Henriksen, Jan-Olav (Dialog, 2015)
Creaturely life is finite life. Transhumanism suggests that human life will be better and even fulfilled in a new way, if humans can overcome some of the finite conditions now given. I argue that there are theological, ethical, and biological points to be taken into consideration that may challenge the transhuman vision of a good life. The finite conditions of human life are what makes human life human, and these conditions are also part of why the deeper meaning of human life is realized in love for others, and not in the quest for making one's own life go on (almost) endlessly. In addition to looking at some material from popular culture and the philosopher Hans Jonas, the article also draws on recent discussions on transhumanism present in contemporary theology.